Refractory Anemia with Ring Sideroblasts Associated with Marked Thrombocytosis Complicated by Massive Splenomegaly Treated with Lenalidomide Resulting in Resolution of Splenomegaly but Severe and Prolonged Pancytopenia - Gordon Taylor; Dominic Culligan; Mark A. Vickers (Case Reports in Hematology)
Refractory anemia with ring sideroblasts associated with marked thrombocytosis (RARS-T) is a hematological malignancy that combines features of both a myeloproliferative and myelodysplastic disorder. There have been recent reports of the successful treatment of anemia in 2 patients with RARS-T with lenalidomide. Here we report the successful treatment of massive splenomegaly in a patient with a long history of RARS-T resulting in complete resolution of splenomegaly, but with prolonged severe cytopenias. We also report the acquisition of the t(3;12)(q26;p13) translocation previously described in cases of myelodysplasia and the potential for transformation to myelofibrosis.